Prospective study of serum selenium concentrations and esophageal and gastric cardia cancer, heart disease, stroke, and total death - Wei, W.Q; Abnet, C.C; Qiao, Y.L; Dawsey, S.M; Dong, Z.W; Sun, X.D; Fan, J.H; Gunter, E.W; Taylor, P.R; Mark, S.D (The American journal of clinical nutrition, 2004)
Background: We previously reported an inverse association between prediagnostic serum selenium concentrations and the risk of esophageal squamous cell carcinoma (ESCC) and gastric cardia cancer (GCC) but not gastric noncardia cancer (GNCC) in a nested study from the Nutrition Intervention Trial in Linxian, China. Objective: We examined the relation between baseline serum selenium and the subsequent risk of death from ESCC, GCC, GNCC, heart disease (HD), stroke, and total death over 15 y of follow-up (1986-2001). Design: We measured baseline serum selenium concentrations in 1103 subjects randomly selected from a larger trial cohort. We identified 516 deaths during the 15-y follow up, including 75 from ESCC, 36 from GCC, 116 from HD, and 167 from stroke. Relative risks (RRs) and 95% CIs were estimated by using Cox proportional hazards regression models. Reported RRs estimated the change in risk conferred by a 25% increase in serum selenium relative to the population distribution. All estimates were adjusted for sex, age, smoking, drinking, and serum cholesterol. Results: We found significant inverse associations between baseline serum selenium and death from ESCC (RR: 0.83; 95% CI: 0.71, 0.98) and GCC (0.75; 0.59, 0.95). Trends toward inverse associations were noted for death from HD (0.89; 0.78, 1.01; P = 0.07), but no association was noted for total death (0.96; 0.90, 1.02) or stroke (0.99; 0.88, 1.11). Conclusion: Population-wide selenium supplementation in the region of China with low serum selenium and high incidences of ESCC and GCC merits serious consideration.